Professor dr hab. Janusz Kacprowski - MALECKI, I. (Archives of Acoustics, 1994)
Polish acousticians suffered a great loss on January 23, 1993, the date of death of Professor Janusz Kacprowski, who passed away after a lengthy and grave disease at age of 76. The entire professional life of prof. Kacprowski was connected with acoustics: a student of the Electrical Department of the Warsaw Technological University before the war in 1939, he continued his education at the underground courses during the German occupation in Warsaw to obtain the M.Sc. degree right after the war in 1945.